(untitled) (Journal of Philosophy Culture and Political Science, 2021)
This article aims to trace the transformation of the Western presence in Central Asia from early independence to present with special attention paid to the United States (US). After the collapse of the USSR, the influence of the West grew significantly, touching numerous spheres in Central Asia, from security and economy to culture and society. The 1990s witnessed domestic political transformations in some Central Asian states in terms of social and political values, reforms of the market system, new ideological and educational platforms, and changing investment strategies. After the 2001 terrorist attack in the US, the security component turned Central Asia into a platform for the Afghanistan operation, and the security component became significant for the Western/US presence in the region. Yet, with the US withdrawal from Afghanistan in 2014, the western strategies towards the region changed significantly, and the region has been rapidly influenced by immediate neighbors such as China and Russia.